Conflict between heterozygote advantage and hybrid incompatibility in haplodiploids (and sex chromosomes) - Ghenu, Ana-Hermina (2019)
The deposited article version is a post-print and is the "Accepted Author Manuscript" provided by Wiley and posted online on 12th January 2018.